Estimasi Karbon Pada Serasah dan Tegakan Dominan di Hutan Produksi Makbon KPHP Kabupaten Sorong - Ponisri Ponisri; Anif Farida (Dinamika Lingkungan Indonesia, 2023)
Litter is one of the places where carbon is stored in forests. It is important to know this because litter indirectly represents CO2 that is not released into the air through combustion. Likewise, vegetation plays an important role in CO2 absorption. Sorong Regency has a forest area that is divided into protected forests, nature reserves, limited production forests, permanent production forests, and convertible forests, as well as business permits for the utilization of timber forest products (IUPHHK). Such physical conditions cause the conditions of CO2 reserves and absorption to change. This study aims to determine litter biomass, carbon, and carbon percentage, and analyze dominant vegetation types in carbon stocks, carbon content, and CO2 absorption. The method used is the non-harvesting sampling method (non-destructive sampling) using allometric equations. The results showed that the highest litter biomass was in line 2, namely 4.571,63 grams with a carbon percentage of 32,940%. Carbon stocks for litter ranged from 0,792-2,149 kg, for a total of 6,523 kg. The dominant species for storing carbon in Makbon production forests are Ficus sp. at the sapling level and Guava/Syzygium sp. at the pole and tree levels.